In vitro Paracoccidioides brasiliensis biofilm and gene expression of adhesins and hydrolytic enzymes - Orlandi Sardi, Janaina de Cassia [UNESP]; Pitangui, Nayla de Souza [UNESP]; Voltan, Aline Raquel [UNESP]; Braz, Jaqueline Derissi [UNESP]; Machado, Marcelo Pelajo; Fusco Almeida, Ana Marisa [UNESP]; Soares Mendes Giannini, Maria Jose [UNESP] (Taylor & Francis Inc, 2015)
Paracoccidioides species are dimorphic fungi that initially infect the lungs but can also spread throughout the body. The spreading infection is most likely due to the formation of a biofilm that makes it difficult for the host to eliminate the infection. Biofilm formation is crucial for the development of infections and confines the pathogen to an extracellular matrix. Its presence is associated with antimicrobial resistance and avoidance of host defenses. This current study provides the first description of biofilm formation by Paracoccidioides brasiliensis (Pb18) and an analysis of gene expression, using real-time PCR, associated with 3 adhesins and 2 hydrolytic enzymes that could be associated with the virulence profile. Biofilm formation was analyzed using fluorescence microscopy, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Metabolic activity was determined using the XTT reduction assay. P. brasiliensis was able to form mature biofilm in 144h with a thickness of 100m. The presence of a biofilm was found to be associated with an increase in the expression of adhesins and enzymes. GP43, enolase, GAPDH and aspartyl proteinase genes were over-expressed, whereas phospholipase was down-regulated in biofilm. The characterization of biofilm formed by P. brasiliensis may contribute to a better understanding of the pathogenesis of paracoccidioidomycosis as well as the search for new therapeutic alternatives; while improving the effectiveness of treatment.
Keywords: adhesins; biofilms; gene expression; Paracoccidioides brasiliensis; real-time PCR; virulence factors